A net-shape forming process of Ti–6Al–4V sphere joints. (20th October 2021) - Zhang, Ce; Pan, Yu; Sun, Jianzhuo; Lu, Xin; Zhang, Jiazhen
ABSTRACT: Near-net shape forming of the hollow sphere joints (60 mm in diameter) used in large space truss structure of spacecraft was realised by powder injection molding and diffusion bonding. For metal injection molding (MIM) process, two binder systems based on polyoxymethylene (POM) and paraffin wax (PW) are comparatively studied. The powder loading, power law index, viscous flow activation energy and integrated rheological factors of feedstock were systematically studied. Except powder loading, The feedstock based on POM system has a smaller strain and temperature sensitivity ( n  = 0.368, E  = 17.95 kJ mol −1 ) and better rheological properties ( α  = 6.3). The lowest interstitials contents of as-sintered samples are 0.05 wt-% for C, 0.28 wt-% for O and 0.046 wt-% for N, which meet the Grade 5 PM (Ti–6Al–4V) specifications according to ASTM B988-13. The tensile strength and ductility reach 978 MPa and 6.3%, respectively, after 1300 °C sintering and capsule-free hot isostatic pressing (HIP).